A special issue only for one virus: Has the football research community responded well to the pandemic? - Meyer, T.; Impellizzeri, F. M. (Science and Medicine in Football, 2021)
Quickly after first lockdown measures were implemented in most countries as a response to the SARS-CoV-2 pandemic, a number of opinion pieces and commentaries was published either advising to be extremely cautious with re-starting football (Corsini et al. 2020) or giving recommendations of how to proceed with training and preparation for competition (DiFiori et al. 2021). Similarly, very negative predictions were issued about the expectable injury burden after the Covid-19 break (Bisciotti et al. 2020). However, none of these texts was data-driven since training and competition had not yet been reinstituted or at least not long enough to enable serious scientific studies. This journal took up the pandemic issue early. It was put into the context of other infectious outbreaks which affected football events (Munoz/Meyer 2020), and a call for submissions for this special issue was accompanied by an editorial explaining why it is necessary to base future decisions on sound data instead of expert opinions only (Impellizzeri et al. 2020). On the next pages, you can find the result of this call.